Factores que influyen en el uso de teléfonos móviles en el contexto de aprendizaje por parte del profesorado de educación superior en la provincia de Santa Catarina (Brasil) (2020)
The purpose of this article is to evaluate the factors that influence the use of cell phones in the context of learning by higher education professors. A descriptive research was carried out with the help of a quantitative survey. The data was obtained through a questionnaire based on the UTAUT 2 model, applied to higher education professors in the province of Santa Catarina, southern Brazil. The UTAUT 2 model is made up of seven independent variables: facilitating conditions, performance expectancy, effort expectancy, social influence, hedonic motivation, price value and habit, in addition to the intention to use dimension, characterized as a dependent variable. Multiple linear regression was used for data analysis. The results show hedonic motivation, performance expectancy, facilitating condition, price value, and habit as factors influencing the intention to use of mobile devices in the researched audience. Price value was revealed as the dimension that most influences the intention to use of mobile devices by professors in class.